The Pathogenesis of Systemic Lupus Erythematosus – An Update - Choi, Jinyoung (2012)
Systemic lupus erythematosus (SLE, lupus) is characterized by a global loss of self-tolerance with activation of autoreactive T and B cells leading to production of pathogenic autoantibodies and tissue injury. Innate immune mechanisms are necessary for the aberrant adaptive immune responses in SLE. Recent advances in basic and clinical biology have shed new light on disease mechanisms in lupus, with this review discussing the recent studies that offer valuable insights into disease-specific therapeutic targets.